1962
DOI: 10.1126/science.138.3545.1104
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Ablation and Passive Avoidance

Abstract: Six rats with bilateral ablation of the hippocampus and six rats with extensive destruction of the neocortex were trained to enter a small compartment, while hungry, for a food reward. After 35 trials, spread over 4 days of training, the animals were given a shock while they were eating in the goal box. After the shock the rats with cortical lesions would not enter the goal compartment on the remainder of the trials given on the same day and only gradually began to re-enter over the next 2 days. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
1

Year Published

1965
1965
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(62 citation statements)
references
References 4 publications
8
53
1
Order By: Relevance
“…It is possible that hyperactivity could affect rate of pressing after the response is learned but bar pressing before acquisition was not affected in the present situation. Since hippocampal-Iesioned animals could not adjust their responding to fit the schedule of reinforcement and consistently -pressed at higher rates than control Ss, these results agree with those reported in other studies (Isaacson & Wickelgren, 1962;Jarrard et aI., 1964) suggesting that hippocampectomized rats are deficient in inhibiting well-learned responses.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is possible that hyperactivity could affect rate of pressing after the response is learned but bar pressing before acquisition was not affected in the present situation. Since hippocampal-Iesioned animals could not adjust their responding to fit the schedule of reinforcement and consistently -pressed at higher rates than control Ss, these results agree with those reported in other studies (Isaacson & Wickelgren, 1962;Jarrard et aI., 1964) suggesting that hippocampectomized rats are deficient in inhibiting well-learned responses.…”
Section: Discussionsupporting
confidence: 83%
“…
AbstraetAcquisition and retention of a food-reinforced barpressing response showed that rats with lesions in the hippocampus consistently pressed at higher rates than both cortical and unoperated control SSe These results cannot be attributed to differences in food motivation or activity since control studies showed food consumption and operant level of bar pressing to be similar.
ProblemRecent studies involving passive-avoidance behavior (Isaacson & Wickelgren, 1962) and extinction of a running response in the runway (Jarrard et aL, 1964) have shown that rats with hippocampal lesions are deficient in inhibiting well-established approach responses to food. These results suggest that one function of the hippocampus may be the inhibiting of well-learned responses.
…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Teitelbaum & Milner (1963), however, have demonstrated that hippocampal lesioned Ss are deficient on this type of avoidance task. Since Kaada et al (1962) report no effect of hippocampal lesions on another type of passive avoidance task, while Isaacson & Wickelgren (1962) report hippocampal lesions to affect this type of avoidance, it would appear that a further breakdown is necessary and possible in hippocampal-septal functions.…”
Section: Resultsmentioning
confidence: 99%
“…Lesions of the hippocampus (e.g., Isaacson & Wickelgren, 1962) and constant septal stimulation (Kasper, 1964) have been shown to decrease passive avoidance behavior. Kasper suggested that septal stimulation produced an avoidance deficit by disrupting a response inhibition circuit in which the hippocampus is critical.…”
mentioning
confidence: 99%